A multi-regional obsidian database for the Eastern Plains. (3rd April 2019) - Jones, Travis W.; Speakman, Robert J.; Billeck, William T.; Hoard, Robert J.
Abstract : Northern and Central Plains obsidian artifacts curated by the Smithsonian Institution's National Museum of Natural History have received little attention by researchers working to understand the nature of long-distance trade, exchange, and interaction. We present the results of a chemical analysis of obsidian stone tools and debitage from these collections. Significant differences in patterns of obsidian use exist between the Northern and Central Plains. Shifts in obsidian use through time within the Central Plains may indicate larger socioeconomic shifts, while obsidian from Northern Plains assemblages suggests an antiquity to interaction networks at least as old as the first Plains Village sites in the region. By creating the first multi-regional obsidian database encompassing parts of the Northern and Central Plains, we expect that the data and our interpretations enhance discussions at the intersection of trade, exchange, and inter-group interaction in the Northern as well as Central Plains.